Marine Ecology Notes - Dormann, Carsten F.; Schroeder, Arne (Open textbook library., 2021)
This books is a general introduction to Marine Ecology, accompanying a lecture and excursion. It targets students without prior knowledge of the subject. The content is taken largely from Wikipedia, but curated and augmented by the authors.